PENGARUH MEDIA TABEL PERKALIAN PINTAR DIGITAL TERHADAP PEMAHAMAN KONSEP MATERI PERKALIAN KELAS IV - Marganis, Pingky Melindia; Handayani, Sri; Prihastari, Ema Butsi (JURNAL SINEKTIK, 2024)
The purpose of this study was to determine whether or not there is an effect of using the Digital Smart Multiplication Table media on the ability to learn Mathematics multiplication material in class IV students of Bayan No. 216 Surakarta State Elementary School. This research is quantitative research with a pre-Experimental Design type. The design used in this research is a one-group pretest-posttest. The subjects in this study were grade IV students. The population amounted to 52 students, while the sample amounted to 28 students. The source of the data obtained is SD Negeri Bayan No. 216 Surakarta. This research data collection technique uses tests, documentation, and observation. While the data analysis technique uses the Kolmogorov-Smirnov normality test and hypothesis testing using Paired Sample T-tests, Based on the results of statistical data with the help of SPSS 29, significant results were obtained, namely 0.001 < 0.05, so Ho was rejected and Ha was accepted, and it was concluded that there was an effect of digital smart multiplication table media on student learning outcomes.